Could face-centered cubic titanium in cold-rolled commercially-pure titanium only be a Ti-hydride?. (15th March 2020) - Chang, Yanhong; Zhang, Siyuan; Liebscher, Christian H.; Dye, David; Ponge, Dirk; Scheu, Christina; Dehm, Gerhard; Raabe, Dierk; Gault, Baptiste; Lu, Wenjun
Abstract: A face-centered cubic (FCC) phase in electro-polished specimens for transmission electron microscopy of commercially pure titanium has sometimes been reported. Here, a combination of atom-probe tomography, scanning transmission electron microscopy and low-loss electron energy loss spectroscopy is employed to study both the crystal structural and chemical composition of this FCC phase. Our results prove that the FCC phase is actually a TiHx ( x ≥ 1) hydride, and not a new allotrope of Ti, in agreement with previous reports. The formation of the hydride is discussed. Graphical abstract: Image, graphical abstract